2018
DOI: 10.1261/rna.066712.118
|View full text |Cite
|
Sign up to set email alerts
|

Coregulation of alternative splicing by hnRNPM and ESRP1 during EMT

Abstract: The epithelial-mesenchymal transition (EMT) is a fundamental developmental process that is abnormally activated in cancer metastasis. Dynamic changes in alternative splicing occur during EMT. ESRP1 and hnRNPM are splicing regulators that promote an epithelial splicing program and a mesenchymal splicing program, respectively. The functional relationships between these splicing factors in the genome scale remain elusive. Comparing alternative splicing targets of hnRNPM and ESRP1 revealed that they coregulate a s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 62 publications
7
51
0
Order By: Relevance
“…Interestingly, several SF-induced spliced isoforms detected in this study (Figure 3 and Table S3), i.e., ARHGEF11+ex38,RALGPS2∆ex10,MLPH+ex9,, and APLP2∆ex7, were previously associated with EMT in mammary epithelial cells (Brown et al, 2011;Harvey et al, 2018;Shapiro et al, 2011;Warzecha et al, 2010), consistent with the invasive phenotype we observe in SF-OE cells.…”
Section: The Splicing Repertoire Of Sr Proteins In Human Mammary Cellsupporting
confidence: 88%
“…Interestingly, several SF-induced spliced isoforms detected in this study (Figure 3 and Table S3), i.e., ARHGEF11+ex38,RALGPS2∆ex10,MLPH+ex9,, and APLP2∆ex7, were previously associated with EMT in mammary epithelial cells (Brown et al, 2011;Harvey et al, 2018;Shapiro et al, 2011;Warzecha et al, 2010), consistent with the invasive phenotype we observe in SF-OE cells.…”
Section: The Splicing Repertoire Of Sr Proteins In Human Mammary Cellsupporting
confidence: 88%
“…hnRNP H might also work as enhancer, if the binding site is downstream the 5′ ss, or inhibitor, if the binding site is located within the exon (Z. Wang & Burge, ). In general, GU‐rich sequences are targets for hnRNP M (Harvey et al, ), G/A motifs are bound by hnRNP A2/B1 and G‐rich sequences are bound by hnRNP F (Huelga et al, ).…”
Section: Splicing Alterations In Cancermentioning
confidence: 99%
“…Aberrant activation of EMT enables primary epithelial cancer cells to acquire advantageous mesenchymal properties, including invasion and drug resistance, ultimately allowing the survival of cancer cells within the circulatory system and subsequent colonization of distant organs [4][5][6] . Whereas several transcription factors, such as Twist, Snail, and Zeb1/2, and signaling pathways, including TGFβ, have been characterized as potent inducers of EMT 6,7 , growing evidence has suggested that alternative RNA splicing acts as a critical layer of regulation impinging on EMT [8][9][10][11] .…”
mentioning
confidence: 99%